The Application of Inclusion-Exclusion in the Collection of Face-to-face Learning Readiness in the Era of Pandemic - Fatimatazzahro, Siti; Fadilah, Nida Muhammad; Azkiya , Ainul (International Journal of Technology and Modeling, 2022)
Face-to-face learning in the COVID-19 pandemic which results in learning activities will be carried out according to the law from government policy, as a result, students are required to vaccinate before face-to-face learning takes place. This study aims to make students able to learn face-to-face using government policy rules and maintain health to break the chain of the covid-19 pandemic, the research method used in this research is descriptive observational using a cross sectional design. The sampling technique used was 67 students who met the inclusion and exclusion criteria by using a questionnaire. The results of the respondent's level using the category of never being sick with COVID-19 of 92.5%, this result is higher than using the category of being exposed to Covid-19, which is only 7.5%. the conclusion of this study is that students have good health to participate in face-to-face learning, there is no relationship between gender, achievement index, but there is a very significant correlation with the area where students live.